Contrasting Life Histories in Neighbouring Populations of a Large Mammal - Mason, Tom H. E. (Public Library of Science, 2011)
BACKGROUND: A fundamental life history question is how individuals should allocate resources to reproduction optimally over time (reproductive allocation). The reproductive restraint hypothesis predicts that reproductive effort (RE; the allocation of resources to current reproduction) should peak at prime-age, whilst the terminal investment hypothesis predicts that individuals should continue to invest more resources in reproduction throughout life, owing to an ever-decreasing residual reproductive value. There is evidence supporting both hypotheses in the scientific literature. METHODOLOGY/PRINCIPAL FINDINGS: We used an uncommonly large, 38 year dataset on Alpine chamois (Rupicapra rupicapra) shot at various times during the rutting period to test these two hypotheses. We assumed that body mass loss in rutting males was strongly related to RE and, using a process-based approach, modelled how male relative mass loss rates varied with age. For different regions of our study area, we provide evidence consistent with different hypotheses for reproductive allocation. In sites where RE declined in older age, this appears to be strongly linked to declining body condition in old males. In this species, terminal investment may only occur in areas with lower rates of body mass senescence. CONCLUSIONS/SIGNIFICANCE: Our results show that patterns of reproductive allocation may be more plastic than previously thought. It appears that there is a continuum from downturns in RE at old age to terminal investment that can be manifest, even across adjacent populations. Our work identifies uncertainty in the relationship between reproductive restraint and a lack of competitive ability in older life (driven by body mass senescence); both could explain a decline in RE in old age and may be hard to disentangle in empirical data. We discuss a number of environmental and anthropogenic factors which could influence reproductive life histories, underlining that life history patterns should not be generalised across different populations.